1998
DOI: 10.1002/(sici)1098-108x(199811)24:3<259::aid-eat3>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Do unsuccessful dieters intentionally underreport food intake?

Abstract: Objective A bogus pipeline paradigm was utilized to assess whether food intake underreporting by unsuccessful dieters is intentional. Method: Twenty‐eight subjects completed 1‐week food diaries. Then, 17 subjects in the experimental condition kept 2‐week food diaries while being told the researcher was verifying their report. Eleven subjects in the control group were asked merely to self‐monitor for two more weeks. Results: Results indicate that subjects in the experimental group reported significantly greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 18 publications
3
34
0
Order By: Relevance
“…Others made enquiries about whether the BP would ever be used in the court room. Taken together with previous successful BP implementations over a wide range of areas (see Jones & Sigall, 1971;Mulheim, Allison, Heshka, & Heymsfield, 1998;Roese & Jamieson, 1993), our information suggests that the BP was genuinely increasing honest responding on our measures. However, it is possible that some men in this study persisted with minimizing their responses even under the BP condition, and that their self-reported belief in the bogus pipeline was simply a product of experimenter expectancy effects.…”
Section: Discussionsupporting
confidence: 80%
“…Others made enquiries about whether the BP would ever be used in the court room. Taken together with previous successful BP implementations over a wide range of areas (see Jones & Sigall, 1971;Mulheim, Allison, Heshka, & Heymsfield, 1998;Roese & Jamieson, 1993), our information suggests that the BP was genuinely increasing honest responding on our measures. However, it is possible that some men in this study persisted with minimizing their responses even under the BP condition, and that their self-reported belief in the bogus pipeline was simply a product of experimenter expectancy effects.…”
Section: Discussionsupporting
confidence: 80%
“…However, it must be underscored that subjects living in a metabolic unit are unlikely to be consuming a diet resembling their typical one, and the unusualness of the diet itself, rather than the knowledge of being observed, may have improved their recall of the diet. Other research using the 'bogus pipeline method', whereby subjects think their true intake is known by observers, seemed to suggest that belief that the investigator 'knows' is only part of the problem 18 . Specifically, the degree of underreporting in a largely overweight subject group was only partially normalised when subjects believed their true energy requirements were being monitored with doubly labelled water.…”
Section: Social Desirability Biases and Obesitymentioning
confidence: 99%
“…The typical procedure is for a subject to write down everything eaten or go through a daily directed-interview process. Numerous studies have shown that people have a tendency to underreport their consumption using these methods (Champagne et al 2002; Glanz et al 1997; Jonnalagadda et al 2000; Lichtman et al 1992; Muhlheim et al 1998; Tooze et al 2004). Estimates of underreporting range from 10 to 30 % for normal weight subjects to 20–50 % for obese adults and children (Champagne et al 2002).…”
Section: Introductionmentioning
confidence: 99%